Innovative Approaches to Robust PID Controller Design for Nonlinear Systems - Singh, Varsha (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 11 No 1&2 (2024): Journal of Advanced Research In Instrumentation Control Engineering, 2024)
Proportional-Integral-Derivative (PID) controllers are widely utilized in industrial applications due to their simplicity and effectiveness in controlling linear systems. However, the adaptation of PID controllers to nonlinear systems presents significant challenges, including oscillatory behavior, instability, and poor performance. This paper explores innovative approaches to enhance the robustness and performance of PID controllers in nonlinear environments. The article begins by outlining the fundamental characteristics of nonlinear systems that pose obstacles to traditional PID control, such as multiple equilibrium points, limit cycles, chaotic behavior, and time-varying dynamics. These complexities necessitate advanced control methodologies capable of handling nonlinearities effectively. Various innovative approaches to robust PID controller design are discussed, including adaptive control techniques, fuzzy logic-based approaches, neural networks, and sliding mode control. Each methodology's theoretical foundations, practical implementation considerations, and real-world applications are examined to highlight their efficacy in addressing the challenges posed by nonlinear systems. Furthermore, the paper discusses the importance of understanding nonlinear system dynamics for effective control design. Techniques such as phase plane analysis, Lyapunov stability analysis, bifurcation analysis, and numerical simulations are explored as essential tools for analyzing and modeling nonlinear behaviors. The limitations of traditional PID controllers in nonlinear contexts are thoroughly examined, emphasizing issues related to parameter tuning, performance degradation, and adaptability. In response to these challenges, adaptive PID control strategies are detailed, including gain scheduling, self-tuning controllers, model reference adaptive control, and integration with machine learning techniques. The practical implementations of these adaptive strategies across diverse industries are illustrated, ranging from chemical process control and renewable energy systems to automotive applications and robotics. Challenges in adaptive PID control, such as design complexity, real-time adaptation, and robustness to disturbances, are also addressed, along with future research directions in integrating advanced machine learning techniques and edge computing for enhanced adaptive control solutions. In conclusion, the article underscores the pivotal role of adaptive PID controllers in mitigating the complexities of nonlinear systems, thereby paving the way for more resilient and efficient control solutions across various industrial domains.